CORRELATION OF MOM'S KNOWLEDGE ABOUT BOOSTER IMMUNIZATION WITH COMPLETE BASIC IMMUNIZATION IN THE WORK AREA OF BOJONG RAWA LUMBU PUBLIC HEALTH CENTER IN 2020 - Lili Farlikhatun; Siarny Dormy Manalu (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
According to WHO, it is estimated that 85% of infants worldwide have been immunized and there are still 19.3% million infants and children who have not been fully vaccinated. Based on data from the Ministry of Health, the coverage of basic immunization shows that of the target number of 4,461,341 infants, the coverage of BCG immunization is 93.8%, DPT 1 69.6%, Polio 1 76.6%, Polio 4 92.4%, measles 91%. With a Drop Out rate of 43.5%, complete basic immunization status for children in West Java Province in 2018 was 57.9%, a slight decrease when compared to Riskesdas 2013 which was 59.2%, while the average value of immunization completeness in Indonesia is 59.2%. Purpose of the study: To find out how the correlation between mother's knowledge about booster immunization and complete basic immunization in the working area of the Bojong Rawa Lumbu Public Health Center in 2020. The population in this study was 73 respondents. The method used was total sampling. The research design used descriptive correlation with a cross approach sectional with chi-square test. There is a relationship between mother's knowledge about booster immunization and the completeness of basic immunization at the Bojong Rawa Lumbu Public Health Center in 2020, with a chi-square result p = 0.000.Keywords: Knowledge, complete basic immunization